Advocating for practical solutions to challenges of Nigerian Party politics - Gar, Ruqayya, Aminu; Katsina, Aliyu Mukhtar; Umar, Mohammed, Nuru; Muhammad, Murtala (My University, 2022)
The major challenges connected to Nigeria’s political party politics includes ideology, corruption, money politics, ethno religious fragmentations, violence and a dominant ruling party with some opposition parties challenging each other. Studies on Nigerian political parties are narrow in advocating for practical solutions to the challenges of party politics in Nigeria, particularly considering the emerging shift in the voting choices of the citizens during the 2007 and 2019 general elections in Bauchi State. This indicates that the influence of political parties on voters appears to be in decline, or at the very least experiencing significant change. Thus, the nature of this evidence of decline and what it means for the future of parties and representative democracy needs to be investigated with realistic way out, which this study aims at through a qualitative method of data collection and analysis. The study concludes that, while political parties are reasonably and normatively important to the process of representative democracy, party politics in Nigeria should embrace a collective viewpoint and common ideology of serving and developing the welfare of the electorates as well as to aggregate, articulate, and stimulate the electorates interests in the form of policy alternatives. In addition, Nigerian political party system must be is a system of connections consequential from inter-party competition. This imply that each party as a component affects and is influenced in turn by the performance of the other parties within Nigeria’s political system.
Keywords: Corruption; Ethno-religious; Fragmentations; Ideology; Money Politics; Nigeria; Party Politics; Practical Solutions